A full service bank how BCCI stole billions around the world - Adams, James Ring; Frantz, Douglas (Simon & Schuster, 1992)
The authors expose BCCI's criminal schemes and its increasingly precarious financial status. The book uses previously unpublished internal bank documents, the minutes of BCCI's executive meetings and extensive interviews.